Pengembangan Media Scrabble Dalam Pembelajaran Bahasa Arab Pada Siswa Kelas VA MI Ismaria Al-Qur’aniyyah Bandar Lampung - Faizatul Aulia, Paliya; Anwar, Khairil; Singgih, Muhammad (Program Studi Pendidikan Bahasa Arab, 2024)
The aim of this research is to determine the design of the Scrabble media that will be used, to determine the feasibility of the Scrabble media and also to determine the effectiveness of the media that has been developed. The questions in this research include